Two Dimensions of Moral Cognition as Correlates of Different Forms of Participation in Bullying - Caravita, Simona C. S.; Finne, Johannes N.; Fandrem, Hildegunn (Frontiers in Psychology, 2022)
The present study investigated whether moral disengagement and the socio-conventional comprehension of aggressions (moral transgressions) are separate dimensions of morality, distinctly associated with different forms of participation in bullying. These two types of moral cognitions have been theorized in different models of morality and are usually studied independently, even if research on moral shifts suggests some possible overlaps. A group of 276 Italian students from primary and middle school (aged 8-15) completed self-reports assessing moral disengagement, socio-conventional perception of moral rules, and participation in bullying as bully, defender of the victim and passive bystander. Results from structural equation modelling analysis indicated that moral disengagement and socio-conventional comprehension of aggressions are separate morality dimensions. Controlling for age and gender, only moral disengagement was associated with perpetrating bullying. These results point at moral disengagement as the critical component of moral cognitions to be addressed in interventions.